2015
DOI: 10.1371/journal.pone.0136730
|View full text |Cite
|
Sign up to set email alerts
|

What Comes First, Job Burnout or Secondary Traumatic Stress? Findings from Two Longitudinal Studies from the U.S. and Poland

Abstract: This longitudinal research examined the directions of the relationships between job burnout and secondary traumatic stress (STS) among human services workers. In particular, using cross-lagged panel design, we investigated whether job burnout predicts STS at 6-month follow up or whether the level of STS symptoms explains job burnout at 6-month follow-up. Participants in Study 1 were behavioral or mental healthcare providers (N = 135) working with U.S. military personnel suffering from trauma. Participants in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
116
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 46 publications
13
116
2
4
Order By: Relevance
“…The two ProQOL subscales were well differentiated, with burnout questions being unrelated to trauma material exposure. The correlation may instead be consistent with burnout and STS having similar risk factors (Cieslak et al 2014), or with burnout contributing to resource depletion and thus increased vulnerability to STS, as suggested by longitudinal studies (Kotaro et al 2015;Shoji et al 2015) and, more generally, the Lazarus and Folkman (1984) stress model. Given self-care, empathy and resilience all negatively predicted burnout in the path analysis, these three predictors could constitute resources which when depleted may no longer offer mitigation of STS development.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The two ProQOL subscales were well differentiated, with burnout questions being unrelated to trauma material exposure. The correlation may instead be consistent with burnout and STS having similar risk factors (Cieslak et al 2014), or with burnout contributing to resource depletion and thus increased vulnerability to STS, as suggested by longitudinal studies (Kotaro et al 2015;Shoji et al 2015) and, more generally, the Lazarus and Folkman (1984) stress model. Given self-care, empathy and resilience all negatively predicted burnout in the path analysis, these three predictors could constitute resources which when depleted may no longer offer mitigation of STS development.…”
Section: Discussionmentioning
confidence: 70%
“…Regarding the relationship between burnout and STS, a meta-analysis of professionals working with trauma survivors (Cieslak et al 2014) found strong associations between burnout and STS, suggesting this may be due to both constructs sharing the same risk factors. Longitudinal studies have found a unidirectional relationship, with earlier burnout predicting increased risk of later STS but not viceversa (Kotaro et al 2015;Shoji et al 2015). Thus, burnout may deplete resources which in turn mitigate STS development, an explanation congruent with Lazarus and Folkman's (1984) theory of stressor appraisal being influenced by, and influencing, coping resources.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Os psicólogos são subme dos constantemente a histórias traumá cas durante sua prá ca profi ssional (Devilly, Wright, & Varker, 2009;Robinson-Keilig, 2014) e o impacto disso para sua saúde mental é pouco explorado. No seu co diano, o psicólogo ouve relatos de traumas, tragédias e perdas, podendo deixá-lo sobrecarregado emocionalmente e acarretar sen mentos de medo, dor e sofrimento, semelhante aos vivenciados pelos seus pacientes (Devilly, Wright, & Varker, 2009;Shoji et al, 2015). Alguns profi ssionais podem ser capazes de tolerar a exposição a fatores de estresse sem manifestações nega vas, enquanto outros são menos tolerantes a essa exposição (Simpson & Starkey, 2006).…”
unclassified
“…Num estudo com 320 psicoterapeutas, Robinson-Keilig (2014) verifi cou que as pessoas que apresentavam altos níveis de ETS nham baixa sa sfação nas relações interpessoais, dificuldades em ter in midade com o outro e padrões de comunicação que envolviam difi culdades de ter uma comunicação constru va, evitando falar dos problemas. Shoji et al (2015) referem que índices altos de síndrome de Burnout predizem o ETS numa amostra de psicólogos clínicos e assistentes sociais. Os psicólogos cons tuem uma categoria profi ssional vulnerável ao adoecimento por ETS, uma vez que suas a vidades envolvem a habilidade empá ca e a escuta constante de histórias traumá cas vivenciadas pelos pacientes (Figley, 1995).…”
unclassified